The Influence of Engineered Tool Surfaces in Ironing - Sulaiman, M.H. (Springer Science and Business Media Deutschland GmbH, 2022)
The present paper focuses on the application of engineered tool surfaces in sheet metal forming. A strip-reduction test was used to investigate the textured tool topographies with small-to-large distances between the pockets in ironing process. An optimum contact area ratio Î± exists at larger speeds, which ensures the effectiveness of the table-mountain structure of the tool topography. The tool texture with a too large amount of pocket area, i.e. with low Î±-value, can reduce the friction and enhance lubrication performance in comparison to that of a finely polished tool surface. Â© 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.